Multi-parameter joint analysis of the quality of honey - Yuan, Yang; Ren, Changshi; Deng, Mengqing; Zhao, Tian; Liao, Yan; Ren, Rongqing; Wang, Hua; Wang, Yinchen (Frontiers in Sustainable Food Systems, 2024)
The scope of this study focused on examining the antioxidant properties and quality of four distinct types of honey from Guizhou province by evaluating various physical and chemical indicators, including total sugar, total phenolic acid, total flavonoid contents, ABTS+, DPPH•, and hydroxyl radical scavenging rate IC50 values, amino acid content, Vitamin B1 and Vitamin C contents, moisture, Baumé degree, color value. The study aimed to comprehensively analyze the factors influencing honey’s antioxidant capacity and quality by integrating physicochemical indicators and farm elevation indicators. Furthermore, correlation analysis, principal component analysis (PCA), and regression analysis were utilized to elucidate the relationships between different parameters in honey and their antioxidant performance. The findings of this study may contribute to a more comprehensive evaluation of honey quality based on multiple parameters and provide valuable insights into the unique characteristics of honey produced in Guizhou province.